(untitled) (European Journal of Interdisciplinary Research and Development, 2023)
This article shows that the need to educate young people spiritually and spiritually, to build a spirit of respect for moral and legal values, and to focus on the pursuit of maturation is an important issue. The socio-legal issue of the relevance of the creation of mechanisms for the formation of loyalty to the National idea, patriotism, high spiritual and moral views, ideological immunity, respect for legal values is covered.